2007
DOI: 10.1074/jbc.m706500200
|View full text |Cite
|
Sign up to set email alerts
|

PII Is Important in Regulation of Nitrogen Metabolism but Not Required for Heterocyst Formation in the Cyanobacterium Anabaena sp. PCC 7120

Abstract: PII is an important signal protein for regulation of nitrogen metabolism in bacteria and plants. We constructed a mutant of glnB, encoding PII, in a heterocystous cyanobacterium, Anabaena sp. PCC 7120, with a cre-loxP system. The mutant (MP2␣) grew more slowly than the wild type under all nitrogen regimens. It excreted a large amount of ammonium when grown on nitrate due to altered activities of glutamine synthetase and nitrate reductase. MP2␣ had a low nitrogenase activity but was able to form heterocysts und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 53 publications
2
45
0
Order By: Relevance
“…strain PCC 7120, previous attempts to inactivate glnB were unsuccessful (26). However, that report was followed by two others in which the obtention of glnB null mutants was described (38,49). In the most recent of these, the authors showed that successful inactivation of glnB could only be achieved when the expression pattern of downstream genes of unknown function was altered (38).…”
Section: Discussionmentioning
confidence: 89%
“…strain PCC 7120, previous attempts to inactivate glnB were unsuccessful (26). However, that report was followed by two others in which the obtention of glnB null mutants was described (38,49). In the most recent of these, the authors showed that successful inactivation of glnB could only be achieved when the expression pattern of downstream genes of unknown function was altered (38).…”
Section: Discussionmentioning
confidence: 89%
“…No PII phosphorylation could be detected in Nostoc punctiforme extracts but the N. punctiforme PII protein could be phosphorylated in vitro by S. elongatus cell extracts (Hanson et al 1998). Mass spectroscopic analysis of the PII protein from Anabaena extracts revealed Tyr51 to be subjected to nitration under diazotrophic conditions while no phosphorylation at Ser49 was detected (Zhang et al 2007). Absence of PII phosphorylation in the Nostocales is, however, in contrast to the presence of a PphA homologue.…”
Section: Modification Of Pii Proteinsmentioning
confidence: 99%
“…NtcA is the main 2-oxoglutarate sensor for the initiation of heterocyst differentiation (239). The otherwise important signal protein PII, which is involved in regulation of nitrogen metabolism in bacteria and plants, is apparently not required for heterocyst formation (240). Nitrogenase synthesis has a high demand for Fe.…”
Section: Occurrence Of Nitrogenases In Heterocystsmentioning
confidence: 99%